2017
DOI: 10.3390/met7040142
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nano-Particles of Niobium Pentoxide with Orthorhombic Symmetry

Abstract: Abstract:In this work, a set of nanoparticles of Nb 2 O 5 nanoparticles were grown by both the Pechini and the sol-gel methods. The amorphous materials were calcined at 650 • C or at 750 • C. X-ray diffraction, scanning electron microscopy, luminescence and Raman spectroscopy were used in order to characterize the materials. From the study, it is possible to state that the method of production of nanoparticles, beyond the temperature of synthesis, has a great influence on whether the phase produced is hexagona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
4
21
0
Order By: Relevance
“…The DRX confirm the production of niobium pentoxide by Pechini method with high crystallinity and free of impurities and the orthorhombic crystalline structure to Nb 2 O 5 , according to PDF 96-210-6535 of ICDD 16,17,18 . In general, the crystallization conditions of each Nb 2 O 5 structure Through analysis of FTIR shown in Figure 2, a band is observed in the region of 832-997 cm -1 that is attributed stretching of the Zn-O band was observed that when Nb 2 O 5 is added that band is shifted and intensified.…”
Section: Characterization Of Niobium Pentoxidementioning
confidence: 63%
“…The DRX confirm the production of niobium pentoxide by Pechini method with high crystallinity and free of impurities and the orthorhombic crystalline structure to Nb 2 O 5 , according to PDF 96-210-6535 of ICDD 16,17,18 . In general, the crystallization conditions of each Nb 2 O 5 structure Through analysis of FTIR shown in Figure 2, a band is observed in the region of 832-997 cm -1 that is attributed stretching of the Zn-O band was observed that when Nb 2 O 5 is added that band is shifted and intensified.…”
Section: Characterization Of Niobium Pentoxidementioning
confidence: 63%
“…The samples were prepared by the polymer precursors method (Pechini method). Aqueous solutions of niobium citrate and metal dopant were prepared following the procedure reported previously in Ref: the metal nitrate at 1% and 2.5% concentrations (manganese nitrate‐Merck, iron nitrate‐Merck and nickel nitrate‐Merk) was completely solubilized in distilled water. Then, niobium chloride (Merck 98%) solubilized in distilled water was incorporated.…”
Section: Methodsmentioning
confidence: 99%
“…Finally the doping with transition metals using sol-gel method, adding metal in situ has been studied in Ref. 14 15 ; then these compounds were tested in photoinduced processes for the degradation of organic compounds, concluding the favorability of the presence of the dopant.…”
Section: Introductionmentioning
confidence: 99%
“…The formed white wet cake was washed with deionized water, transferred to a glass beaker, and dried in vacuum oven for 48 h at 135°C (WOCT-135) to ensure that all the organic solvents were removed. The dried cakes were placed in a porcelain crucible for calcination at 1050°C for 3 h in a muffle furnace (WOCT-1050) 61,62 . The annealed grey metal oxide was milled and further used after washing in ethanol and distiller water (WOCT) in this study (photo all the extraction process shown on the Supplementary Fig.…”
Section: Mineral Extractionmentioning
confidence: 99%